Influence of Customer Complaint Management on Marketing Performance of Banks - Grace U. Oru; Humphrey Ikenna Madumere (ARRUS Journal of Social Sciences and Humanities, 2022)
Leveraging the cognitive dissonance and attribution theories, this study examined the influence of customer complaint management on the Marketing performance of banks in Afikpo. Applying marketing performance from the lenses of the customer, 323 bank customers were involved in the study. Copies of questionnaire were used to elicit responses from the customers after a test of reliability and validity on the questionnaire. Collected data were analyzed with SPSS Version 21.0, simple regression analysis. Results indicate that the customer complaint based on management constructs (accessibility, responsiveness, integration) significantly influence marketing performance of bank. The study therefore recommends among others that banks should design complaint management systems that are simple and understandable for customers, while being fair, efficient, and responsive in complaint handling.